Altered Fetal Head Growth in Preeclampsia: A Retrospective Cohort Proof-Of-Concept Study - Eviston, David P.; Minasyan, Anna; Mann, Kristy P.; Peek, Michael J.; Nanan, Ralph K. Heinrich (Frontiers in Pediatrics, 2015)
Background Preeclampsia is associated with fetal growth restriction and low birth weights. Neurotrophins, which mediate neuronal growth and development, are also increased in the placenta and cord blood in preeclampsia. Hence, the aim of this study was to determine whether fetal head growth is altered in preeclampsia, adjusting for growth restriction and other confounding variables. Methods This research included a retrospective cohort study, looking at fetal head circumference at birth, plus a case control study examining fetal head circumference at mid-gestation. The head circumference at birth analysis consisted of 14,607 pregnancies (preeclampsia=382, control=14,225), delivered between 7/2006-6/2012 at Nepean Hospital, Australia. Head circumference at birth, in addition to other maternal and fetal variables, was sourced from the Nepean Obstetric Database. The head circumference at mid-gestation study consisted of 756 pregnancies (preeclampsia=248, control=508), delivered within the same data collection period at Nepean Hospital. Head circumference at mid-gestation was retrieved from an earlier ultrasound scan. Exclusion criteria included >1 fetus, illegal drug use, alcohol consumption, chronic or gestational hypertension. Generalised linear models (GLM) were used to analyse fetal head circumference in preeclampsia versus controls, adjusting for confounding variables. Results Head circumference increased at a greater rate in preeclampsia versus controls, adjusted for gestation, fetal gender, birth weight and length, smoking, maternal BMI and growth restriction. At mid-gestation, there was no difference in head circumference between preeclampsia and controls. Conclusions For the first time, this research has suggested increased fetal head growth in preeclampsia, adjusted for confounders. This finding may be explained by altered fetal exposure to neurotrophins in preeclampsia. The long term neurodevelopmental consequences of preeclampsia remains unclear.